Modelling Of CMOS Based Interleaved PN Junction Optical Phase Shifters - Javid Shaikh, Abdurrahman (2019)
The performance of an optical interconnect depends on the underlying optical modulator design. Performance of these modulators is largely influenced by the embedded optical phase shifters. Among several topologies, depletion-mode interleaved junction phase shifters are most promising because of the high speed associated with depletion mode of operation and high modulation efficiency associated with interleaved junction structure. Due to structural complexity of interleaved topology, the phase shifter performance depends on several design parameters. Also, intricate trade-offs exist among various performance metrics with respect to these design variables. For viable modulator design, optimization is necessary which requires performance predictive models. In the literature, only preliminary numerical research has been pursued to understand the behaviour of such a promising topology, that too, with many simplifying unrealistic assumptions. Interleaved junction phase shifters, however, require rigorous three-dimensional (3D) modelling for true description of the modulator performance. Such 3D mathematical predictive models are absent in the literature. In this thesis three dimensional optoelectronic simulations, incorporating physics-based models and adequate correction models, have been performed to obtain rigorous numerical results. The overall workflow is divided in three stages. Industry standard tools from Lumerical Inc. based on Finite-Difference-Frequency-Domain (Lumerical MODE Solutions), Finite-Element-Modelling (Lumerical DEVICE TCAD), and Finite-Difference-Time-Domain (Lumerical FDTD Solutions) have been used for waveguide (stage 1), device (stage 2) and phase shifter (stage 3) performance modelling respectively. Nonlinear predictive models are then obtained by pursuing careful, stage-wise curve fitting procedures using MATLAB 2015b. For the first time, comprehensive mathematical guidelines for the passive design of submicron rib waveguides have been proposed along with mathematical predictive models for modulation efficiency, capacitance per unit length, and bandwidth of the optical phase shifters. The accuracy of the models have been compared against the foundry fabricated designs. An estimation error of about 7% or below was noted for all the proposed models. Such models would enable application specific optimization of submicron silicon interleaved PN-junction optical phase shifters.